If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-13-n=n+3
We move all terms to the left:
-13-n-(n+3)=0
We add all the numbers together, and all the variables
-1n-(n+3)-13=0
We get rid of parentheses
-1n-n-3-13=0
We add all the numbers together, and all the variables
-2n-16=0
We move all terms containing n to the left, all other terms to the right
-2n=16
n=16/-2
n=-8
| 19c=5-2 | | 3z2–22z–16=0 | | X/100=6/25x | | 24r-8=22r+132 | | (2^½)^x+7=(2^2)^x | | x-73=-4x+87 | | 3x-1(2x+9)=10 | | 2(x+60)+2(30)=200 | | 1.7n=1.36 | | 3x-1(2x+9=10) | | -171-4x=117+5x | | (x/2)+2x/3=5/6 | | -171-4x=117 | | 6(x+5)=3(x-2 | | -9+2x=3x-6 | | 8(k)=20 | | 10,000-255x=2,500+10x | | -94+8x=50+4x | | 4/5=2x/50 | | -44-15x=28-13x | | 3x=1=4x-2 | | 102÷4=3m | | 250=189-w | | 10,000-255x=2,500+100x | | 3m×4=102 | | 4w+12=80 | | 12^x=240 | | 10,000-25x=2,500+100x | | -32-7x=-2x+58 | | 5x+61=98.8 | | -300+2(x+6)=8x+120 | | 2(x+60)+(30)=200 |